Hydromorphology of the Unconfined Groundwater in the South of Klaten District (Data Before Earthquake Mei 27th 2006) - Langgeng Wahyu Santosa (Forum Geografi, 2006)
There are some characteristics and distributions of unconfined groundwater variation in the research area. Those are related to a system of water supply and consumptive use for drinking water. Variation of the groundwater characteristic depends on variation of morphology. Therefore, it is needed to delineate hydromorphology units of the regions as a base on groundwater resources management, especially for drinking water. The aims of the research are: (1) to study of the characteristic and distribution of unconfined groundwater variations base on landform units, (2) to study the factors that affect such variations, and (3) to establish the hydromorphology units of the regions for groundwater resources management, especially for drinking water. The method used in this research is landform approach and field survey. The sampling method is stratified sampling, based on landform as the analysis approach. Result of the research shows that there are some variations of groundwater characteristic at each landform. Landforms which have good groundwater characteristic are Hydromorphology Unit of Fluvio Volcanic Plain of Young Merapi (except Bayat region) and Hydromorphology Unit of Volcanic Foot Plain of Young Merapi. At those units, there are good quality of groundwater, bicarbonate water (hydrochemical type I), having low electric conductivity, shallow of water table, low in fluctuation, and middle to fast class in aquifer permeability. Those units are the most potential unconfined groundwater resources management for drinking water. The units which have poor groundwater characteristic are Hidromorphology Unit in Bayat Region, including Undulating Alluvial Plain, Fluvio Volcanic Plain of Young Merapi, and Swamp Alluvial Plain. Generally, the groundwater quality is medium to poor, the hydrochemical type is Va (initiation process of connate water) and type III (evaporate water), shallow up to medium of water table, and low to middle class of aquifer permeability. The taste of groundwater is brackish to saline with high concentration of chloride.